BUILDING CIVIC ENGAGEMENT THROUGH THE "NO VIRAL NO JUSTICE" PHENOMENON - Elsa Grecya; Ilham Effendi Yahya (Journal Civics And Social Studies, 2022)
This research aims to analyze public spaces that are indirectly open to the public and influence the course of law. This research method was carried out using the library research method. The data sources used are secondary data sources in the form of journals and online news articles. The research results show that the police are considered to have failed in carrying out their role as services and protectors of the community. The no viral no justice phenomenon has become a hard blow to the Indonesian National Police. National Police Chief General Pol Listyo seems to admit that the hashtag no viral no justice is not just a fad hashtag. Listyo Sigit Prabowo asked his staff to make this phenomenon part of the public's criticism of the police. Listyo appealed to prevent police-related phenomena from recurring. He asked staff to evaluate and improve themselves in serving the community. Listyo reminded that all public assessments must be accepted as part of the police's criticism and assessment. Apart from this, indirectly the no viral no justice phenomenon opens up alternative public spaces through social media. This public space is used by the community as opinion leaders from the community who indirectly form civic engagement based on pity for the victims and disappointment with the police who have failed in carrying out their duties.